Cambial Activity of Moringa peregrina (Forssk.) Fiori in Arid Environments - Gärtner, Holger; Farahat, Emad (Frontiers in Plant Science, 2021)
Moringa peregrina (Forssk.) Fiori, one of 13 species of the Moringaceae family widely distributed throughout the dry tropics, has the potential to become one of the most economically important medicinal plants in Egypt. However, despite its tolerance for drought and heat, it is also threatened by increasing temperatures and decreasing precipitation. Although the phenophase of this species is well documented, almost nothing is known about its period of cambial activity in desert regions. Ring formation and the general environmental adaptability of trees are affected by the timing of cambial activation. In our study site, we observe a distinct coupling of the development of new green leaves at the onset of vegetative growth in October and the phase of cambial activity (November – January). The onset of cambial activity seems to be related to a drop in temperature in October and the onset of torrential rains in the region. There might even be a short phase between the end of cambial activity and the onset of bud formation without xylem formation, but with photosynthetic activity. If so, we assume that all assimilates are stored as non-structural carbohydrates (NSC) in the parenchyma of the new ring. This potential gap opens new questions regarding the correlation between NSC storage capacity and the timing of remobilization for subsequent ring formation.